Summary of International Recommendations for Donation and Transplantation Programs During the Coronavirus Disease Pandemic. Issue 1 (January 2021) - Weiss, Matthew J.; Lalani, Jehan; Patriquin-Stoner, Chelsea; Dieudé, Mélanie; Hartell, David; Hornby, Laura; Shemie, Sam D.; Wilson, Lindsay; Mah, Allison
Abstract : Background: The COVID-19 pandemic has disrupted all aspects of the international organ donation and transplantation (ODT) system. Multiple organizations have developed guidance, but to date, no comparative summary has emerged to understand differences in existing recommendations. Methods: We developed and applied a comparative methodology to a convenience sample of recommendations available on The Transplantation Society website. Document types were classified according to characteristics such as type of organization (eg, governing body or professional society) and geographic region. Recommendations were grouped according to content, and summaries were posted on a public website. This process is ongoing and will be updated as new recommendations become available. Results: Eighteen documents were extracted in the initial review. All documents were based on expert opinion, and none described a formal literature review or adherence with clinical guideline development processes. Recommendation categories included screening of potential donors, risk assessment of potential recipients, posttransplant risk, living/paired donation, protection of ODT professionals, and ethics/logistics. While many documents included similar recommendations, such as the need to screen and test patients who are potential donors, there was variation on some topics. Type of recommended laboratory testing varied with 64% recommending nasopharyngeal swabs, 43% oropharyngeal, and 24% bronchial aspirates. Updated results are available at https://cdtrp.ca/en/covid-19-international-recommendations-for-odt/ Conclusions: The current state of COVID-19 ODT recommendations is limited to expert opinion. Substantial variation exists regarding recommendations, which are based on emerging but currently low-quality evidence. This summary of existing recommendations will serve to inform priorities for evidence-based recommendations. Abstract : Supplemental Digital Content is available in the text.